2014
DOI: 10.3233/jad-140168
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cancer and Alzheimer's Disease: Systematic Review and Meta-Analysis

Abstract: This study examined the association between cancer and Alzheimer's disease (AD) by a quantitative meta-analysis of cohort studies. Studies were identified by searching PubMed database through 1966 to December 2013 using the terms "Alzheimer's disease", "neoplasm", and "cancer". Six studies met the inclusion criteria in the overall meta-analysis. We pooled effect sizes using fixed-effects and random-effects models. Furthermore, we also tested for heterogeneity and publication bias. The results suggested that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 0 publications
3
54
2
Order By: Relevance
“…A recent meta-analysis reported the existence of an inverse association between cancer and AD (Ma et al, 2014). We offer several cautions about this analysis.…”
Section: Discussionmentioning
confidence: 82%
“…A recent meta-analysis reported the existence of an inverse association between cancer and AD (Ma et al, 2014). We offer several cautions about this analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Several other studies have reported lower risks of AD diagnosis before and after overall cancer diagnosis or for particular cancer sites . The findings for subpopulations, however, vary across studies.…”
Section: Discussionmentioning
confidence: 89%
“…While diabetes is a known modifiable risk factor for both dementia and cancer, the association between cancer and dementia remains uncertain. Population‐based cohort studies have reported inconsistent risk levels for dementia among individuals with cancer . We therefore conducted a cross‐sectional survey using a prospective Japanese cohort to examine whether having cancer or comorbid cancer and diabetes from midlife increases the risk of physician‐diagnosed dementia.…”
Section: Risks Of MCI Dementia and Cd After Incidence Of Cancer Or mentioning
confidence: 99%